Downregulated GPR30 expression in the epileptogenic foci of female patients with focal cortical dysplasia type IIb and tuberous sclerosis complex is correlated with 18F‐FDG PET‐CT values. (10th February 2021) - Wang, Zhongke; Huang, Kaixuan; Yang, Xiaolin; Shen, Kaifeng; Yang, Ling; Ruan, Ruotong; Shi, Xianjun; Wang, Miao; Zhu, Gang; Yang, Meihua; Zhang, Chunqing; Lv, Shengqing; et al.
Abstract: Focal cortical dysplasia type IIb (FCDIIb) and tuberous sclerosis complex (TSC) are typical causes of developmental delay and refractory epilepsy. G‐protein‐coupled receptor 30 (GPR30) is a specific estrogen receptor that is critical in neurodevelopment, neuroinflammation, and neuronal excitability, suggesting that it plays a potential role in the epilepsy of patients with FCDIIb and TSC. Therefore, we investigated the role of GPR30 in patients with FCDIIb and TSC. We found that the expression of GPR30 and its downstream protein kinase A (PKA) pathway were decreased and negatively correlated with seizure frequency in female patients with FCDIIb and TSC, but not in male patients. GPR30 was widely distributed in neurons, astrocytes, and microglia, and its downregulation was especially notable in microglia. The GPR30 agonist G‐1 increased the expression of PKA and p‐PKA in cultured cortical neurons, and the GPR30 antagonist G‐15 exhibited the opposite effects of G‐1. The NF‐κB signaling pathway was also activated in the specimens of female patients with FCDIIb and TSC, and was regulated by G‐1 and G‐15 in cultured cortical neurons. We also found that GPR30 regulated cortical neuronal excitability by altering the frequency of spontaneous excitatory postsynaptic currents and the expression of NR2A/B. Further, the relationship between GPR30 and glycometabolism was evaluated by analyzing the correlations between GPR30 and 18 F‐FDG PET‐CT values (standardized uptake values, SUVs). Positive correlations between GPR30 and SUVs were found in female patients, but not in male patients. Intriguingly, GPR30 expression and SUVs were significantly decreased in the epileptogenic tubers of female TSC patients, and ROC curves indicated that SUVs could predict the localization of epileptogenic tubers. Taken together, our results suggest a potential protective effect of GPR30 in the epileptogenesis of female patients with FCDIIb and TSC.